A Striking Response to Lithium in Kleine–Levin Syndrome - Sveinsson, Olafur (Frontiers in Neurology, 2014)
Kleine-Levin syndrome (KLS) is an episodic hypersomnia with cognitive disturbances such as confusion, apathy and derealisation. Hyperphagia and hyper sexuality occur in around 50% of cases. No evidence-based treatments have been established for Kleine Levin syndrome. Many drugs have been tried, most often with little success. Here a case with a striking response to lithium is presented.